1989
DOI: 10.1093/brain/112.6.1637
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Event-Related Potentials in Multiple Sclerosis

Abstract: Twenty-three patients with multiple sclerosis (MS) and 1 patient with isolated optic neuritis (mean age 37.5 yrs, average duration of disease 10 yrs) were tested with auditory and visual cognitive event-related potentials (ERPs) using an oddball paradigm. The results were compared with data from 19 age-matched healthy controls. All patients had magnetic resonance imaging (MRI) head scans and 19 had comprehensive neuropsychological testing. The stimulus-related components of the ERPs were normal for nearly all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 0 publications
3
37
1
2
Order By: Relevance
“…Newton et al 14 found an incidence of 57% of cognitive potential alterations that included delays in wave latencies and lack of its characteristic morphology. Dijk et al 15 did not find differences in event-related evoked potentials in a group of 30 patients with MS, with an incidence of 15.6% of wave peak absence of all the potentials assessed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Newton et al 14 found an incidence of 57% of cognitive potential alterations that included delays in wave latencies and lack of its characteristic morphology. Dijk et al 15 did not find differences in event-related evoked potentials in a group of 30 patients with MS, with an incidence of 15.6% of wave peak absence of all the potentials assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Newton et al 14 reported that event-related evoked potential generation would be, in part, dependant on white matter integrity, and mild degrees of cognitive dysfunction would not always be detected by intellectual capacity assessment tests, thus the possibility of objective tests, carried out by event-related evoked potentials become a useful tool in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] One study in which the N1 and P2 potentials were reportedly affected is that of Giesser et al, 20 but this was in demented as compared with non-demented patients. More recently, Hendler et al 21 found long latency AEPs to be abnormal only in conjunction with bilaterally abnormal short latency potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Os achados encontrados nesta pesquisa referentes à presença de alterações no P300 em indivíduos com EM, bem como ao tipo de alteração mais freqüentemente encontrada neste potencial, ou seja, atraso na latência da onda P300, são compatíveis com os obtidos por Newton et al (1989), Giesser et al (1992), Gil et al (1992), Dijk et al (1992) …”
Section: Parte II -Resultados Do Potencial Evocado Auditivo De Médiaunclassified